2015
DOI: 10.1007/s11111-015-0231-x
|View full text |Cite
|
Sign up to set email alerts
|

Political fragmentation and land use changes in the Interior Plains

Abstract: Recent years have witnessed growing interest in the critical role of local/regional governance structures in shaping physical land development and associated natural resource management processes. This article investigates how political fragmentation in local governance can affect land use patterns through a watershed-level analysis of population and employment density changes in the Interior Plains, the largest physiographic division of the U.S. Population density change rates are found to be negatively assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…A lower value generally indicates a higher degree of decentralization (or political fragmentation), with a more evenly distributed pattern of government expenditures among municipalities. A higher value of HHI suggests that the spending is dominated by a single jurisdiction in the region, that is, political power concentration (see, for example, Grassmueck and Shields 2010; Hendrick, Jimenez, and Lal 2011; Kim, Cho, and Keane 2015). Recent studies have suggested that political fragmentation in local/regional governance can lead to a more sprawling pattern of development (see, for example, Byun and Esparza 2005; Carruthers and Ulfarsson 2002; Kim, Cho, and Keane 2015; Razin and Rosentraub 2000).…”
Section: Analysis Of Contextual Factors—sample Data and Methodologymentioning
confidence: 99%
“…A lower value generally indicates a higher degree of decentralization (or political fragmentation), with a more evenly distributed pattern of government expenditures among municipalities. A higher value of HHI suggests that the spending is dominated by a single jurisdiction in the region, that is, political power concentration (see, for example, Grassmueck and Shields 2010; Hendrick, Jimenez, and Lal 2011; Kim, Cho, and Keane 2015). Recent studies have suggested that political fragmentation in local/regional governance can lead to a more sprawling pattern of development (see, for example, Byun and Esparza 2005; Carruthers and Ulfarsson 2002; Kim, Cho, and Keane 2015; Razin and Rosentraub 2000).…”
Section: Analysis Of Contextual Factors—sample Data and Methodologymentioning
confidence: 99%
“…Additionally, each metropolitan area’s governance structure was measured using the following three indicators. The first metric (PCGOV) is the total number of government units per capita in each metropolitan region, which has been widely used in other empirical studies on political fragmentation and its implications (e.g., Hawkins and Dye, 1970; Kim et al., 2015; Ulfarsson and Carruthers, 2006). A greater value of this variable (i.e., a higher number of government agencies per resident) means that each government unit covered fewer residents, indicating a higher degree of political fragmentation.…”
Section: Methodology and Datamentioning
confidence: 99%
“…A greater value of this variable (i.e., a higher number of government agencies per resident) means that each government unit covered fewer residents, indicating a higher degree of political fragmentation. Specifically, the calculation is as shown in equation (1): The second indicator is the so-called Hirschman–Herfindahl Index (HHI), which has been employed in some recent studies (e.g., Grassmueck and Shields, 2010; Hendrick and Shi, 2015; Hendrick et al., 2011; Kim et al., 2015). Public expenditure information from the Census of Governments was used for this measure; therefore, this index represents the degree of fiscal concentration/decentralization within an MSA, as shown in equation (2): HHI has a value ranging from 1/ n ( n denotes the number of local government units in a region) to 1.0, where 1/ n represents a perfectly even distribution of public spending among local government units, and 1.0 represents the opposite extreme, which indicates the highest level of concentration in government spending patterns.…”
Section: Methodology and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This cumulative set of decisions have contributed to low-density growth patterns that has, in turn, led to a range of increasingly challenging issues, including increasing congestion, rising infrastructure costs, decreasing air quality, loss of open space, and increases in greenhouse gas emissions (Kim, Cho, and Keane, 2015;Pendall, 1999).…”
Section: Introductionmentioning
confidence: 99%